Successful extracorporeal membrane oxygenation resuscitation of patient with cardiogenic shock induced by phaeochromocytoma crisis mimicking hyperthyroidism: A case report - Wang Tao (De Gruyter, 2021)
A 29-year-old woman presented to the emergency department with the acute onset of palpitations, shortness of breath, and haemoptysis. She reported having an abortion (56 days of pregnancy) 1 week before admission because of hyperthyroidism diagnosis during pregnancy. The first diagnoses considered were cardiomyopathy associated with hyperthyroidism, acute left ventricular failure, and hyperthyroidism crisis. The young woman’s cardiocirculatory system collapsed within several hours. Hence, venoarterial extracorporeal membrane oxygenation (VA ECMO) was performed for this patient. Over the next 3 days after ECMO was established, repeat transthoracic echocardiography showed gradual improvements in biventricular function, and later the patient recovered almost completely. The patient’s blood pressure increased to 230/130 mm Hg when the ECMO catheter was removed, and then the diagnosis of phaeochromocytoma was suspected. Computed tomography showed a left suprarenal tumour. The tumour size was 5.8 cm × 5.7 cm with central necrosis. The vanillylmandelic acid concentration was 63.15 mg/24 h. Post-operation, pathology confirmed phaeochromocytoma. To our knowledge, this is the first case report of a patient with cardiogenic shock induced by phaeochromocytoma crisis mimicking hyperthyroidism which was successfully resuscitated by VA ECMO.